Genotype-by-environment interaction studies for yield and Aspergillus resistance in groundnut (Arachis hypogaea) using AMMI and GGE biplots - YADAWAD, ARATI; BHAT, RAMESH (The Indian Journal of Agricultural Sciences, 2026)
The present study was carried out during rainy (kharif) and summer seasons of 2019, 2020 and 2021 at three test locations of Dharwad, Belagavi and Bagalkot districts of Karnataka intended to assess the genotype by environment interaction (GEI) effects to identify high yielding and stable lines with Aspergillus resistance in groundnut (Arachis hypogaea L.) through AMMI and GGE biplots. Seventy-four advanced groundnut lines (F4–F6) derived from the cross between, GPBD 4, Spanish bunch variety resistant to rust and LLS but highly susceptible to Aspergillus infection and ICGV 2266, tolerant to Aspergillus infection were field evaluated. Multi environmental trials were conducted at three locations namely Dharwad, Bagalkot and Belagavi districts of Karnataka following randomised complete block design (RCBD) with two replications. Significant variability was revealed for pod yield, shelling percentage and Aspergillus infection percentage at individual locations and seasons. Pooled analysis of variance revealed highly significant (p<0.001) influences of Genotype (21.70%) and GEI (37.37%) on pod yield. In contrast, shelling percentage and Aspergillus infection percentage revealed high environmental influence of 93.24% and 55.04%, respectively with limited impacts of genotype and GEI. AMMI and GGE biplot models identified seven adaptable lines for high pod yields across the environments. G19 line was identified as potential high yielding line (4165.23 kg/ha) with low Aspergillus infection and two lines (66 and 43) showed high pod yields along with low Aspergillus infection percentage indicating the potential of these lines for development of promising groundnut varieties with high yields and tolerance to Aspergillus infection. Line 59 showed least Aspergillus infection percentage (29%) and can serve as a valuable genetic resource in future Aspergillus flavus resistance breeding programmes.